MEKANISME KLIRING PADA PERBANKAN KONVENSIONAL PERSPEKTIF ISLAM - Abdul Salam (JESI (Jurnal Ekonomi Syariah Indonesia), 2012)
Abstract Clearing is derived from English "to clear" meaning settlement, while the meaning of the clearing is good electronic financial data between banks or between the client resolved calculation results in a certain time. In the implementation of this clearing, clearing services client in this exploit is represented by the bank. Thus, in Islam the activity is often called as wakalah. The aim of this study is to find out how the mechanism clearing system running on Conventional Banks, and how Islamic outlook about the system, including categories of interest or not. In this research, the writer uses descriptive analysis method and more closer to study literature (library research) plus a little interview with employees of the Bank. The results of study that emphasize the study of this literature is the case of the grant of the bank overdraft services require customers to refund loan of approximately 5% above the highest rate in the bank in a month. In the same cases, Bank gives sanction to the customer to check for empty and termination of client giral blacklisted by a bank. This could be allowed under Islam law, due to before dropping the sanctions, warning that the banks were giving our customers don’t draw a blank check anymore. Keywords: Clearing Mechanism, wakalah, overdraft, Conventional Banks, Islamic perspective